The Use of a New Benzothiadiazole Derivative for the Control of Cercospora Leaf Spot in Sugar Beet and Its Effect on the Yield - Agnieszka Kiniec; Maciej Spychalski; Rafal Kukawka; Katarzyna Pieczul; Adrian Zajac; Marcin Smiglak (Agriculture)
The use of plant protection products (PPPs) is the main method of controlling Cercospora leaf spot (CLS), as it constitutes a cheap and effective approach that is easy for farmers to follow. Unfortunately, it is widely recognized that the use of PPPs poses a risk not only to the environment but also to human health. The urgent need for sustainable development, recommended by the European Union and expressed in the “Farm to Fork Strategy”, includes a serious restriction on the use of PPPs. This strategy assumes a 50% reduction in the use of PPPs by 2030. These efforts have driven the exploration of innovative and effective plant protection strategies utilizing new active compounds. The examined substance, N-methyl-N-methoxyamide-7-carboxybenzo(1.2.3)thiadiazole (BTHWA), is a novel amide derivative of benzothiadiazole with the ability to induce systemic acquired resistance (SAR). This work presents a series of experiments conducted in the process of determining the appropriate technology for BTHWA use and proving its effectiveness in controlling CLS in sugar beet cultivation. It has been demonstrated that the application of treatments using BTHWA or BTHWA combined with a fungicide in a reduced number of treatments had the same effect on the reduction of plant infection with C. beticola and obtained root and technological sugar yields the same as those that resulted from the use of a full fungicidal treatment. The results provide grounds for reducing the use of fungicides by showing that the same effects can be attained by combining or replacing them with BTHWA.